Il successo scolastico dei giovani figli dell’immigrazione: il ruolo della famiglia come capitale sociale - Grasso, Maria (Rivista Italiana di Educazione Familiare, 2015)
Compared to the processes of social integration of young people from immigrant families, the family as an index of social capital can be configured both as a promotional resource and as a negative agent with respect to the results of success or failure in school and more deeply to the processes of inclusion or exclusion. The diversity of family models and of migration experiences does not always guarantee the necessary conditions of containment and support in the growth process. Factors such as insecurity, loneliness, the trauma of migration can adversely affect the life paths. Politics and society must take charge of equalization of future Italian citizens and school acts as a driver of inclusion and support to students but also to their families, through opportunities for active participation.